2017
DOI: 10.22260/isarc2017/0049
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Using Advanced Visualization Tools for Residential Property Management

Abstract: -Traditional real estate business models are not able to attract young generation customers since they are used to acquire required information from digital apps and devices. This paper aims to develop a framework for application of advanced visualization technology in residential property marketing to offer a detailed 3D information model to customers through the real estate websites. The paper presents the result of a survey examining the experience of customers who were used one of the five selected real es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…These are physical and tangible components of any system, which combine in a systematic way to achieve value for a product or service [131]. Gadgets used in real estate include those for digital story telling that rely on augmented information [132], collaborative decision making through VR and BIM integration [133], real-time tracking for near-miss accidents [134] and as-built modelling using Lidar and 3D laser scanning [135], among others. Various data collection tools and gadgets have been developed over the years to augment real estate practices.…”
Section: Data Collection Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These are physical and tangible components of any system, which combine in a systematic way to achieve value for a product or service [131]. Gadgets used in real estate include those for digital story telling that rely on augmented information [132], collaborative decision making through VR and BIM integration [133], real-time tracking for near-miss accidents [134] and as-built modelling using Lidar and 3D laser scanning [135], among others. Various data collection tools and gadgets have been developed over the years to augment real estate practices.…”
Section: Data Collection Technologiesmentioning
confidence: 99%
“…A recent study that involved a survey of online real estate platforms concluded that by using these advanced visualisation tools, property managers could communicate more easily with consumers, and consumers could examine properties more easily from the point of view of their requirements without a physical inspection. 3D modelling, views and pictures provide customers with more credible and reliable property information that is mutually beneficial to key stakeholders: property owners, consumers and real estate agents [135]. Another application of 3D scanning relates to heritage conservation and recording [150].…”
Section: D Scanningmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, virtual 3D models of the buildings have created a significant enhancement in the marketing process for presenting the building's specifications to the customers. The property owners, customers, real estate agents, and other stakeholders benefit from these virtual 3D models [39]. It should be noted that the 3D models do not replace the experience of the customers to walk through their desirable units, feeling the spaces, and observe the outside views.…”
Section: Marketing Paradigm In Multi-story Apartment Buildingsmentioning
confidence: 99%